Opinie polskich wyborców na temat integracji europejskiej i wprowadzenia waluty euro w kontekście kryzysu finansowego w Europie i na świecie - Musiał-Karg, Magdalena (Political Preferences, 2013)
The main aim of this paper is the analysis of the opinions of the Polish society on the European integration process and introduction of the euro currency in Poland. The research problem seems to be very interesting due to the fact that before and few years after the Polish accession to the EU, people's attitudes towards integration and European currency were very enthusiastic. The opinions of Polish electorate had radically changed by the end of 2008, when the Poles began to feel the negative results of the economic slowdown caused by the global financial crisis. The analysis was made in the context of party preferences in Poland and the data cover three periods: December 2004, December 2008 and the last quarter of 2012.